Synthesis, characterization, mesomorphic and electrical properties of tetrakis(alkylthio)-substituted lutetium(III) bisphthalocyanines - Atilla, Devrim; Kilinc, Necmettin; Yüksel, Fatma; Gürek, Ayşe Gül; Ozturk, Zafer Ziya; Ahsen, Vefa (Elsevier Science Sa, 2009)
The synthesis of new lutetium(III) bisphthalocyanines substituted with alkylthio groups (1-5) is described. These compounds (Pc2Lu) are soluble in most common organic solvents and have been fully characterized (elemental analysis, FT-IR, UV-Vis spectroscopy, mass spectrometry). The thermal stabilities of the Pc compounds were determined by thermogravimetric analysis (TGA). The mesogenic properties of these new materials forming columnar-hexagonal (Col(II)) mesophases were studied by differential scanning calorimetry (DSC), optical microscopy and X-ray diffraction. The compounds 2-5 exhibit a double clearing point. DC electrical properties of these compounds in different phases were determined by measuring I-V characteristics and dark current of their thin films on interdigital electrodes. The measurements were carried out in ambient air, in vacuum and in high purity nitrogen (N-2) flow in the temperature range between 300 and 420 K. Dark current measurements obtained in the crystal, liquid crystal (LC) and isotropic liquid phases were in agreement with the phase transitions of these compounds obtained by DSC and optical microscopy results. The relation between the phase transition and conductivity of the Pc2Lu derivatives were investigated. Also, the influence of the nature of the substituted group (alkylthia and alkoxy) upon the DC electrical properties of the Pc2Lu derivatives was investigated. The DC conductivities and the thermal activation energies depending on alkyl chain lengths of these compounds were found to be in the range of 10(8) to 10(-5) S/cm and 0.12-0.38 eV in solid phase. Crown Copyright (C) 2008 Published by Elsevier B.V. All rights reserved.
Keywords: Lutetium phthalocyanine; Lanthanide; Thin films; Dark current conductivity; Liquid crystal